The effect of flaxseed extract on genes expression during wound healing process in rabbit - Ahmad Nazri, Aliah; Mustafa Al-Ahmad, Basma Ezzat; Mokhtar@Makhtar, Khairani Idah; Lestari, Widya; Sha'ban, Munirah; Abdul Qader, Omar Abdul Jabbar (2019)
Background: Wound healing is a natural response to tissue injury and it involves regulated order of cellular and biochemical actions to reinstate tissue after injury, that involves resurfacing, reconstitution, and restoration of tensile strength of injured skin. Most of the chemical medications which widely used for wound healing that might cause unwanted side effects with prolong use such as hyper scarring, thus studies using natural products are now deem important. Flaxseed is a natural product that enhances the immune system functioning against different diseases. Nevertheless, limited studies have been done looking into the response triggered by immune cells and the wound-healing related genes with the use of flaxseed extract onto the wounded skin for healing process. Objectives: This study was conducted to analyze the genes expression during different stages of wound healing process in rabbit. Materials and Methods: Twenty seven male New Zealand rabbits were randomly divided into three groups of 9 rats: Flaxseed treated (study group), 2% Fucidin cream treated (positive control), and the negative control group which received no treatment. Flaxseed extract was prepared according to standard ethanol extraction protocol and was applied to wound. Full thickness wounds with 15 mm in length were made in both sides of backbone. Tissue samples were obtained at the end of 4, 7 and 14 days from all groups for RNA extraction. Total RNA then subjected for Reverse Transcription-PCR to detect the expression of wound healing-related genes (IL6, IFN-γ, MMP9, TGF-β, and VEGF). The levels of expression are determined by using GAPDH as internal positive control. Results: Expression of flaxseed treated wound was observed to be higher compared to positive and negative control for IL-6, MMP-9 and IFN-γ while expression of VEGF are more observed only in non-treated wounds. The level of TGF-β is expressed almost in the same manner for fucidin and flaxseed treated. Conclusion: Flaxseed extract caused changes in the level of wound healing-related genes expression is corresponded with the different phases of healing process. This supported the potential of using flaxseed extract as one of the possible treatments for wound healing.